Analysis of bZIP gene family in lotus (Nelumbo) and functional study of NnbZIP36 in regulating anthocyanin synthesis - Ping Zhou; Jingwen Li; Huiyan Jiang; Qijiang Jin; Yanjie Wang; Yingchun Xu (BMC Plant Biology, 2023)
Abstract Background The basic leucine zipper (bZIP) family is a predominant group of transcription factors in plants, involved in regulating plant growth, development, and response to stressors. Additionally, the bZIP gene family has a key role in anthocyanin production. Despite the significant role of bZIP genes in plants, their potential contribution in lotus remains understudied. Results A total of 124 bZIP genes (59 NnbZIPs and 65 NlbZIPs) were identified from genomes of two lotus species. These genes were classified into 13 groups according to the grouping principle of the Arabidopsis bZIP gene family. Analysis of promoter cis-acting elements indicated that most bZIP gene family members in lotus are associated with response to abiotic stresses. The promoters of some bZIP genes contain MYB binding sites that regulate anthocyanin synthesis. We examined the anthocyanin content of the petals from three different colored lotus, combined with transcriptome data analysis and qRT-PCR results, showing that the expression trends of NnbZIP36 and the homologous gene NlbZIP38 were significantly correlated with the anthocyanin content in lotus petals. Furthermore, we found that overexpression of NnbZIP36 in Arabidopsis promoted anthocyanin accumulation by upregulating the expression of genes (4CL, CHI, CHS, F3H, F3'H, DFR, ANS and UF3GT) related to anthocyanin synthesis. Conclusions Our study enhances the understanding of the bZIP gene family in lotus and provides evidence for the role of NnbZIP36 in regulating anthocyanin synthesis. This study also sets the stage for future investigations into the mechanism by which the bZIP gene family regulates anthocyanin biosynthesis in lotus.